Methodology of analysis by high performance liquid chromatography (hplc) for the quantification of stevioside and rebaudioside a. In different varieties of stevia sp. From cultivate of fundo America in Santa Rita Siguas Arequipa - Gonzalo Dávila del Carpio (2019)
The objective was to identify a line of Stevia sp. with high concentrations of total glycosides and rebaudioside A, from cultivate of Fundo América in Santa Rita Siguas- Arequipa, to propagate it at commercial scale. Participating entities were Fundo América and UC SM, with support from the Program of Science and Technology (FINCyT). Samples of leaves were selected to identify Stevia rebaudiana Bertoni and Stevia puberula hybrids by DNA extraction and amplification with RAPD markers, identifying molecular markers for each one. Three hybrids of Stevia were selected by its higher content of stevioside and rebaudioside A: TU-12, TU-13 and TR-14, using a new method developed in the research through isocratic elution with NH2 columns by HPLC. The proportion found between percentage of stevioside and rebaudioside-A was 7,62%-8,01%, 8,11%-8,56% and 9,33%- 4,21% for the varieties TU-12, TU-13 y TR-14, respectively. Molecular analysis of the three hybrids showed than TU-12, TU-13 and TR-14 had a percentage of similarity with Stevia rebaudiana of 38.8%, 29.4% and 30% respectively. The micropropagation of Stevia, reached in total 6393 seedlings produced in vitro. After adaptation in greenhouse, were carried to field, achieving a production at 103 days in first harvest of 1300 kg/ha. of dried leaves. If we consider that the yield in the first harvest is 70% of total yield (3 harvest cuttings in total), we are talking about an approximate yield of 6850 kg/ha. The content analysis showed that stevioside and rebaudioside need more time to adapt and increase the concentration of both glycosides.